2019
DOI: 10.1002/ange.201814104
|View full text |Cite
|
Sign up to set email alerts
|

Control of Excited‐State Conformations in B,N‐Acenes

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…This is in agreement with the studies of Lu et al. in 2019, [16] who showed that, the large Stokes shift is due to the twisting of the C 2 B 2 N 2 core in the diazadiboranapthalenes 6 in the excited state, which can be prevented in different matrices. Interestingly, our phosphorescence measurements showed a short‐lived phosphorescence of all diazadiboratriphenyles 7 a – h between 12.5 and 15.0 msec (see Supporting Information for details).…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the studies of Lu et al. in 2019, [16] who showed that, the large Stokes shift is due to the twisting of the C 2 B 2 N 2 core in the diazadiboranapthalenes 6 in the excited state, which can be prevented in different matrices. Interestingly, our phosphorescence measurements showed a short‐lived phosphorescence of all diazadiboratriphenyles 7 a – h between 12.5 and 15.0 msec (see Supporting Information for details).…”
Section: Figuresupporting
confidence: 93%
“…Recently, our group reported a synthetic route to diazadiboranaphthalenes 6 and investigated their photophysical properties [16] . In these studies, we were able to show that the diazadiboranaphthalenes 6 exhibits two solvent‐dependent emissions, and the one at longer wavelength was attributed to a twisted intramolecular charge transfer (TICT).…”
Section: Figurementioning
confidence: 99%